Celebrities in the Recruitment of Candidates for Legislative Members of the Indonesian Parliament in the Legislative Elections - M. Dwi Sugiarto; Yuwanto Yuwanto (JURNAL ILMU SOSIAL, 2020)
The 2019 Legislative Election featured many celebrities involved in the contestation, where a total of 11 of the 16 political parties had legislative candidates from the celebrity circles. Democratic National Party (NasDem) became the party that nominated most celebrities as legislative candidates. Armed with the popularity that has made celebrities attract political parties to nominate them to increase the vote acquisition and even the number of seats. The process of recruiting legislative candidates from celebrities by the NasDem Party is the focus of this research on how the approach and process are carried out. The study uses qualitative analysis with a descriptive approach to describe the process that occurs through interviews and review of documents and news as a source of data. The results obtained indicate that the NasDem Party’s legislative candidate was recruited using an approach that involved the NasDem Party elite and fellow celebrities as intermediaries. Factors driving celebrities to become the NasDem Party’s legislative candidates are moral support (debriefing, fostering, and active interaction with party elites) and material (Campaign Props, campaign costs, financial reimbursement), Indonesian Restoration slogans, and anti-dowry politics, as well as egalitarian politics attitudes. Celebrity-related research in politics has focused a lot on the role of transformation from entertainment to politics. In contrast, this research has focused on recruiting celebrities as legislative candidates by the NasDem Party.